Performance Evaluation of Artificial Angular Fly Ash Aggregate - Yadav, Yogesh; Saud, Ishwor Singh (Journal of Advanced College of Engineering and Management, 2023)
This experimental study describes the development of the lightweight angular fly ash aggregate (FAA) and consequent comparison of properties of FAA with natural aggregate (gravel). The manufacturing process of these FAA involves blending of fly ash with cement and alkali activators at various proportioning of cement to fly ash and placing the mix in the mould. This is followed by curing of the cubes for 7 days after letting it to dry for 24hrs and crushing them to obtain the aggregate of different sizes. After having the fly ash aggregate, the test are carried out in fresh state and hardened state of the fly ash aggregate concrete and the conventional concrete. Results are compared to see the efficiency level of flyash aggregate concrete.The properties of both angular fly ash aggregates like Specific gravity, water absorption, Impact value, and Abrasion value are compared with the properties of the conventional aggregates (gravel). This study concludes that FAA with proper mix proportioning can be used as a substitute for conventional aggregates for sustainable construction.